Basal cell carcinoma. Diagnostic and therapeutic recommendations of Polish Dermatological Society - Aleksandra Lesiak; Joanna Czuwara; Grażyna Kamińska-Winciorek; Dorota Kiprian; Joanna Maj; Witold Owczarek; Waldemar Placek; Lidia Rudnicka; Piotr Rutkowski; Michał Sobjanek; Małgorzata Sokołowska-Wojdyło; Jacek Szepietowski; et al. (Przegląd Dermatologiczny, 2019)
Incidence of skin cancers is constantly increasing, what constitutes a significant epidemiologic problem of modern medicine. Basal cell carcinoma is the most common neoplasm affecting Caucasians. Histopathological examination is a gold standard that allows for diagnosing skin cancers. The presented recommendations discuss clinical and pathomorphological sub-types of basal cell carcinoma, their dermoscopic features, stage assessment, and methods for treatment as well as prevention of recurrence of this cancer. Surgical excision of the lesion is a basic and preferred therapeutic option. Other non-surgical options show lower treatment efficacy, and thus, should be considered in cases of cancers with low risk of recurrence, when a surgery is contraindicated or impossible.